Analysis of the Effect of Olfactory, Approach Behavior, and Experiential Marketing toward Purchase Intention - Cherish Anggie; Jony Oktavian Haryanto (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2011)
The drive of retail business competition is getting tighter and causing retailers to seek to entice consumers to be regular and faithful at their stores. Retailers need to understand consumer behavior in order to obtain what is desired by consumers. Therefore, consumer behavior needs to be studied considering various factors which can influence consumer decisions to buy a product. The emergence of BreadTalk in Indonesia in the bakery industry with a different concept bakery store has caused rapid development in this industry. One strategy used by BreadTalk to encourage consumers to visit, feel the different experience, and ultimately to increase consumer purchase intention is to use dimensional olfactory as one of the elements in the store ambience. With this phenomenon, this study aims to find the significant influence of the olfactory, approach behavior, experiential marketing toward purchase intention. Collecting data in this study was done by spreading questionnaires to students of the University of Pelita Harapan, who had visited and shopped at BreadTalk Supermal Karawaci. The questionnaires were distributed to 150 respondents. The variables that exist in the study are measured using the Likert scale. The sample collection technique used was a non-probability sampling technique of sampling with a purposive sampling method. The data are then processed by using reliability analysis, validity, and methods of structural equation modelling analysis. From the results of this study the significant influence from olfactory to 3 variables mentioned above can be seen.